Institutional Barriers to Inclusive Assessment for Students with Special Needs in Indian Higher Education - Kushwaha, Ravindra Kumar; Maurya, Hemant Kumar (Khwopa Journal, 2024)
This study examines the institutional barriers to implementing inclusive assessment strategies for students with special needs in Indian higher education. Given the crucial role of inclusivity in educational equity, this research aims to identify and analyse the systemic hindrances that restrict the practical application of inclusive assessment methods in universities across India. The objectives of this study are twofold: firstly, to explore how institutional policies, resource allocation, and faculty awareness affect the inclusion of students with special needs; and secondly, to propose actionable strategies that can mitigate these barriers. The methodology employed consists of a mixed-methods approach, integrating both qualitative and quantitative data. Surveys were distributed to faculty members and administrators across multiple universities to assess their perspectives on and experiences with inclusive assessments. Additionally, in-depth interviews were conducted with selected stakeholders, including policy-makers, educators, and students with special needs, to gain a deeper understanding of the institutional challenges. Findings indicate that significant barriers include inadequate faculty training on special needs, limited financial resources dedicated to inclusive education tools, and inflexible academic policies that do not accommodate diverse learning requirements. Moreover, a general lack of awareness and understanding of special needs among university staff exacerbates these challenges, leading to insufficient support for implementing effective inclusive assessment strategies. The study concludes with recommendations for enhancing faculty training programs, revising institutional policies to be more accommodating, and increasing funding for resources necessary for inclusive education. These strategies aim to foster a more supportive and equitable educational environment for all students, regardless of their special needs.